1977
DOI: 10.1139/m77-024
|View full text |Cite
|
Sign up to set email alerts
|

The role of metabolic energy in the lethal action of basic proteins on Candida albicans

Abstract: Comparative studies were made on the destructive effects of certain basic proteins on a strain of Candida albicans and two of its respiration-impaired mutants. Both by direct plate counts of survivors and by quantitative ultraviolet spectrophotometric analyses of released cellular constituents, the respiration-impaired mutants were less vulnerable to the destructive actions of the basic proteins than were ordinary wild-type cells. The lethal incidence and the ultraviolet absorbing cellular substances released … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 14 publications
0
13
1
Order By: Relevance
“…In the present study we investigated the molecular mechanism underlying the long known phenomenon that energy depletion in yeast induces resistance against cationic peptides and proteins (1). At variance with the generally accepted explanation that implies a role for ATP-driven transport systems, we found that energy depletion induces membrane rigidification, possibly mediated by the cytoskeleton, which desensitizes C. albicans to antimicrobial peptides.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In the present study we investigated the molecular mechanism underlying the long known phenomenon that energy depletion in yeast induces resistance against cationic peptides and proteins (1). At variance with the generally accepted explanation that implies a role for ATP-driven transport systems, we found that energy depletion induces membrane rigidification, possibly mediated by the cytoskeleton, which desensitizes C. albicans to antimicrobial peptides.…”
Section: Discussionmentioning
confidence: 81%
“…This promotes their insertion into and transmigration over the cytoplasmic membrane of the target cell, with killing of the cell as a final consequence. Interestingly, cellular sensitivity to cationic proteins and peptides such as salivary histatins and defensins is diminished by conditions that affect the energy status of the target cell (1)(2)(3)(4)(5)(6). This effect is not restricted to cationic peptides, because azoles are also sensitive to the energy status of Candida glabrata (7).…”
mentioning
confidence: 99%
“…Miller noted that comparable cell homogenates from murine macrophages had no bactericidal activity (38). However, cationic proteins and perhaps other granule constituents as well might act as ancillary antifungal mechanisms, enhancing effects of oxidative mechanisms (39). While these studies have not yet identified all mechanisms active in killing of hyphae by normal monocytes, the data using monocytes from both myeloperoxidase-deficient and one of the four chronic granulomatous disease patients suggest the existence of potent myeloperoxidase-independent or nonoxidative antihyphal systems.…”
Section: Resultsmentioning
confidence: 99%
“…Decreased susceptibility to Hsts is a common feature of anaerobically grown C. albicans (Table 1), respiratory (petite) mutants (17), or cells pretreated with azide or the proton ionophores CCCP and DNP (23). In yeast, proton ionophores uncouple respiratory chain phosphorylation and induce endogenous fermentation; azide functions dually as a respiratory inhibitor and uncoupler (25,27,29,39). It is notable that cells with reduced susceptibility to Hst 5 lack or have inhibited mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%